Trust in public performance information: The effect of data accessibility and data source - Schmidthuber, L., Willems, J.and Krabina, B. (Public Administration Review)
Building on transparency literature, we theorize that information characteristics such as accessibility of raw data and data source provision influence citizens' trust in public performance information. Next to the question of whether providing a data source matters, we argue that information provision from a non-government actor can compensate for the information asymmetry between citizens and public sector organizations due to a stronger symmetric data exchange relationship. Integrating and elaborating these theoretical assumptions of principal-agent theory with bureaucratic reputation theory, the organization's reputation, rather than the stakeholder group the information provider is belonging to, may explain varying trust. We conduct eight online experiments in large-N data collections in Austria and Germany and find that data accessibility and source provision increase trust in performance information. Whereas citizens have more trust in government-provided data compared to data provided by other citizens, source reputation matters dominantly for building trust in performance information.- Reproduced